DEVELOPING STUDENTS' SUBJECTIVITY AS AN IMPORTANT ASPECT OF FOREIGN LANGUAGE TEACHING - Vyshnevska, Maryna (Collection of scientific papers «ΛΌГOΣ», 2023)
In the field of foreign language pedagogy, the cultivation of students' subjectivity is a crucial yet underexplored facet in the attainment of communicative competence and cultural competence. While conventional methodologies in language education have focused primarily on linguistic structures and communicative skills, the importance of fostering learner subjectivity remains underrepresented in pedagogical discourse. A burgeoning body of scholarly literature acknowledges the indispensability of subjective engagement in language learning and emphasizes its profound implications for fostering intrinsic motivation, intercultural sensitivity, and holistic linguistic development. However, empirical research and systematic frameworks that elucidate the intentional cultivation of students' subjectivity in the context of foreign language teaching remain remarkably scarce.